PARADIGMA INTEGRATIF DALAM PEMBELAJARAN IPA MI - Irham Nugroho (Al Ibtida: Jurnal Pendidikan Guru MI, 2016)
ABSTRACT Knowledge is intrinsically comes from Allah SWT which is revealed to Prophet Muhammad SAW and is embodied in Al Qur’an. Paradigm is a group of values which form one’s thought as his or her starting point of view so that it will form one’s subjective image – about a reality – which finally will determine how this one responds the reality. Human should not ever stop thinking about him/her self, his/her surrounding, and (the most important) The Creator. Islam taught its followers to always undertake studies on behavior or any rotation and changes happen, either on natural phenomenon or what happen amongst human beings.   Science teaching in Madrasah Ibtidaiyah (Islamic Elementary School) should instill moral values that educate students to become caracterized. It can be undertaken by science teaching using integrated bayani, burhani, and irfani approach. Keyword: science teaching, integrated bayani burhani irfani approach.